(untitled) (International Journal of Engineering and Computer Science, 2014)
In the current trends of the world, the technologies have advanced so much that most of the individuals prefer using the internet as the primary medium to transfer data from one end to another across the world. The data transition is made very simple, fast and accurate using the internet. However, one of the main problems with sending data over the internet is the security threat it poses i.e. the personal or confidential data can be stolen or hacked in many ways. Therefore it becomes very important to take data security into consideration, as it is one of the most essential factors that need attention during the process of data transferring. There are many research processing techniques related to internet security, cryptography and steganography etc. One of these is data-hiding, using this concept we can provide security, authentication to the system. Data hiding cannot recover original cover. While Reversible data hiding is a novel concept, which can recover original cover without any loss of image. With Reversible Data Hiding (RDH) we can perform embedding operation after encryption. In this technology initially a content-owner creates space for embedding additional data and then encrypts the original image after that data hider module embed additional data in the space created in the encrypted image. At the receiver side, host can extract the data and additional data and recover original message. This concept improves payload & security of the system. This is the basic theme of this concept. Basically this work describes the survey of the reversible data hiding techniques, related methods and procedures that have been developed with the subject.